2020
DOI: 10.34259/ijew.20.7012226
|View full text |Cite
|
Sign up to set email alerts
|

Speech Sources Separation Based on Models of Interaural Parameters and Spatial Properties of Room

Abstract: This paper presents the extended evaluation in different reverberant scenarios for different mixtures of speech having interfere at one of the six angles {15 0 , 30 0 , 45 0 , 60 0 , 75 0 , 90 0 } of the model which implementing spatial covariance with interauralaparameter for improving the performance of MESSL.Thetbinaural spatialtparameters, such as interauralaphase difference IPD and interauralalevel difference ILD and spatialacovariance areamodeled in the short-timeaFourieratransform. The parametersaof the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In [20], Andre reported that Wang and Brown model needs to be improved. The ICA method can be used for separation if two sources of mixture are available assuming that the two signals from the two different sources are statistically independent [123,124,132,133,137]. In [19], Takigawa tried to improve the performance of W & B model.…”
Section: H I Tmentioning
confidence: 99%
“…In [20], Andre reported that Wang and Brown model needs to be improved. The ICA method can be used for separation if two sources of mixture are available assuming that the two signals from the two different sources are statistically independent [123,124,132,133,137]. In [19], Takigawa tried to improve the performance of W & B model.…”
Section: H I Tmentioning
confidence: 99%